Effects of technological improvement in the ICT producing sector on business activity - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 2006)
It seems to be taken for granted by many commentators that the sharp decline in prices of computers, telecommunications equipment and software resulting from the technological improvements in the information and communications technology (ICT)-producing sector is good for jobs and is a major driving force behind the non-inflationary employment miracle and booming stock market in the latter half of the nineties in the U.S. and their recurrence since 2004. We show that, in our model, a technical improvement in the ICT-producing sector by itself cannot explain a simultaneous increase in employment and a rise in firms’ valuation (or Tobin’s Q ratio). There are two cases. If the elasticity of equipment price (pI ) with respect to ICT-producing sector’s productivity is less than one, labor’s value marginal productivity increases thus pulling up the demand wage and expanding employment. However, the increased output by adding to the capital stock and thus driving down future capital rentals causes a decline in firms’ valuation, q per unit, even though Tobin’s Q (= q=pI ) is up. If the elasticity is greater than one, equipment prices fall so dramatically that labor’s value marginal productivity declines, employment in the ICT-using sector expands proportionately more than the increase in capital stock, thus raising future capital rentals, so both firms’ valuation and Tobin’s Q rise; but then real demand wage falls and employment contracts. The key to generating a booming stock market alongside employment expansion is to hypothesize that when technical improvement in the ICT-producing sector occurs, the market forms an expectation of future productivity gains to be reaped in the ICT-using sector. Then we can explain not only the stock market boom and associated rise in investment spending and employment in the period 1995-2000 but also the subsequent decline in employment, in Tobin’s Q and in investment spending in 2001, with consumption holding up well as productivity gains in the ICT-using sector were realized. An anticipation of a future TFP improvement in the ICT-using sector can once more play the role of raising the stock market.